MENINGKATKAN KARAKTER ANAK MELALUI PEMBINAAN KARAKTER RELIGIUS DI STASI HATI TAK BERNODA SANTA PERAWAN MARIA WUTUNGLOLO-KROKOVOLOR - Yakobus Belo Tobi; Maria Gelu; Hendrikus Boli; Skolastika Lelu Beding (Adiba Aisha Amira, 2026)
Community Service (PkM) activities targeting children at the Santa Perawan Maria Wutunglolo-Krokovolor Hati Tak Bernoda Station are one of the most important activities in fostering children's religious character. This can be done because currently many children have minimal religious character. They behave badly, are not active in spiritual activities such as prayer at KBG, do not attend mass on Sundays. In addition, they always use dirty words, are dishonest, undisciplined, always disobey parents and teachers' orders, and often fight. This activity can be carried out so that it aims to improve the religious character of children at the Santa Perawan Maria Wutunglolo-Krokovolor Hati Tak Bernoda Station through religious character development. This activity takes place for 3 months starting from September-October 2025 and ends with the provision of development materials on October 25, 2025. The method used in this activity is a development and participatory method. The results of the Community Service activities are that the religious character of the children at the Santa Perawan Maria Wutunglolo-Krokovolor Hati Tak Bernoda Station is improving, and they are realizing the importance of religious character in their daily lives. They are increasingly involved in spiritual activities and drawing closer to God through their words and actions. They are able to implement religious character in accordance with Catholic values ​​towards others wherever they are. The children's religious character is firmly rooted in the teachings of the Catholic Church and will become outstanding individuals in the future.